1984
DOI: 10.1530/jrf.0.0710581
|View full text |Cite
|
Sign up to set email alerts
|

Production in vitro of mouse early pregnancy factor and purification to homogeneity

Abstract: Early pregnancy factor (EPF) has been produced in vitro by culture of oestrous mouse oviducts and ovaries in RPMI, with the addition of prolactin and mouse embryo culture medium. The pooled harvested medium was then subjected to immunoabsorption, electrofocusing and gel filtration. A fraction was isolated with pI 6.83 and molecular weight 21 000 which was responsible for 90% of the recovered biological activity. It appeared to be homogeneous when analysed by high-performance gel-permeation chromatography. SDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

1984
1984
1997
1997

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 11 publications
(13 reference statements)
1
30
0
1
Order By: Relevance
“…EPF can be detected in the rosette inhibition test in concentrations at least as low as 100 pg ml~l, i.e. 20 pg in 0·2 ml sample (Cavanagh 1984), while significant binding of labelled EPF to spleen cells is not observed below 2 ng in 0 . 2 ml sample (10 ng ml-I concentration).…”
Section: L-----~----~2------*3----~4mentioning
confidence: 92%
See 4 more Smart Citations
“…EPF can be detected in the rosette inhibition test in concentrations at least as low as 100 pg ml~l, i.e. 20 pg in 0·2 ml sample (Cavanagh 1984), while significant binding of labelled EPF to spleen cells is not observed below 2 ng in 0 . 2 ml sample (10 ng ml-I concentration).…”
Section: L-----~----~2------*3----~4mentioning
confidence: 92%
“…With EPF isolated from sheep serum (fetal EPF) ' Wilson et al (1983) could detect 1 ng ml-I in the assay with sheep lymphocytes and anti-sheep lymphocyte serum. Cavanagh (1984) found that, with mouse lymphocytes and anti-mouse lymphocyte serum, 100 pg ml-1 mouse maternal EPF would give a positive result. With the same assay system, A. C. Cavanagh (unpublished data) compared material purified from mouse and human tissue and found that human EPF was 10 2 -10 3 times more active in the assay than was mouse EPF.…”
Section: Purification Of Epfmentioning
confidence: 97%
See 3 more Smart Citations